Wannier threshold theory for the description of the two-electron cusp in the ion-induced double ionization of atoms - Barrachina Tejada, Raul Oscar (2016)
The double electron capture into the continuum states of the projectile (double ECC) is investigated theoretically in collisions of 100 keV He2+ ions with He atoms. The process is described within the framework of the impact parameter and frozen-correlation approximations where the single-electron events are treated by the continuum distorted wave method. On the other hand, the Wannier theory is employed for describing the angular correlation between both ejected electrons. This treatment substantially improved the agreement between the theory and experiment as compared to the previous version of the theory (Gulyás et al., 2010) in which the correlation between the ejected electrons was taken into account by the Coulomb density of states approximation.